The effect of bank credit and the trade patterns of Colombian exporters - Mónica Roa; Danielken Molina (Banco de México, 2017)
In this paper we use manufacturing data on Colombian exports and bank financing to estimate the credit elasticity of exports. The data allows us to construct a supply side instrumental variable for the credit of manufacturers that we use to address a possible reverse causality problem. We find that access to credit produces a significant increase in the revenue of exporters, explained by the positive effect of credit on the trade margins. Likewise, we find that across manufacturers, the impact of credit on the margins varies by firm size. Medium-sized manufacturers use credit to increase their market reach, market penetration and product mix. The largest manufacturers use credit to increase their market reach, while the smallest manufacturers use it to expand their product mix.
Keywords: F14; G21; 330; International Trade; Export Margins and Bank Financing